Visualization of the infection risk assessment of SARS-CoV-2 through aerosol and surface transmission in a negative-pressure ward. (April 2022) - Guo, Weiqi; Fu, Yingying; Jia, Rui; Guo, Zhendong; Su, Chen; Li, Jiaming; Zhao, Xiuguo; Jin, Yifei; Li, Penghui; Fan, Jinbo; Zhang, Cheng; Qu, Pengtao; et al.
Graphical abstract: Abstract: Since December 2019, coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a great challenge to the world's public health system. Nosocomial infections have occurred frequently in medical institutions worldwide during this pandemic. Thus, there is an urgent need to construct an effective surveillance and early warning system for pathogen exposure and infection to prevent nosocomial infections in negative-pressure wards. In this study, visualization and construction of an infection risk assessment of SARS-CoV-2 through aerosol and surface transmission in a negative-pressure ward were performed to describe the distribution regularity and infection risk of SARS-CoV-2, the critical factors of infection, the air changes per hour (ACHs) and the viral variation that affect infection risk. The SARS-CoV-2 distribution data from this model were verified by field test data from the Wuhan Huoshenshan Hospital ICU ward. ACHs have a great impact on the infection risk from airborne exposure, while they have little effect on the infection risk from surface exposure. The variant strains demonstrated significantly increased viral loads and risks of infection. The level of protection for nurses and surgeons should be increased when treating patients infected with variant strains, and new disinfection methods, electrostatic adsorption and other air purification methods should be used in all human environments. The results of this study may provide a theoretical reference and technical support for reducing the occurrence of nosocomial infections.